2019
DOI: 10.1002/asia.201901140
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Anisotropy in CoIIX4 (X=O, S, Se) Single‐Ion Magnets: Role of Structural Distortions versus Heavy Atom Effect

Abstract: Mononuclearf our coordinate Co II complexes have drawn ag reat deal of attention as they often exhibit excellent single-ion magnet (SIM) properties. Among the reported complexes, the axial zero-field splitting parameter (D)w as found to vary drastically both in terms of the sign as well as strength. There are variousp roposals in this respects uch as structural distortions,h eaviera tom substitution, metalligand covalency,t uning secondary coordination sphere, etc. that are expected to control the D values. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
(46 reference statements)
2
24
0
Order By: Relevance
“…on this complex predicted a very large negative D value of −70 cm −1 [9a] . Magneto‐structural correlations performed on this type of {CoS 4 } system by us and others further revealed that the magnetic anisotropy of these complexes is controlled by the following factors: i) structural parameters such as bond angle and torsional angle around the first and second coordination sphere atoms, [12c, 39] ii) effect of donor atoms or ligand field strength, [39b, 40] iii) spin‐orbit coupling of the donor atoms [41] and also iv) counterions [39d, 42] . Soft donor groups such as S, Se/Br, I coordination bring down the 4 A 2 → 4 T 2 (ligand field states in T d symmetry) transition energy gap, and thus the D switches to negative from positive.…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 70%
See 2 more Smart Citations
“…on this complex predicted a very large negative D value of −70 cm −1 [9a] . Magneto‐structural correlations performed on this type of {CoS 4 } system by us and others further revealed that the magnetic anisotropy of these complexes is controlled by the following factors: i) structural parameters such as bond angle and torsional angle around the first and second coordination sphere atoms, [12c, 39] ii) effect of donor atoms or ligand field strength, [39b, 40] iii) spin‐orbit coupling of the donor atoms [41] and also iv) counterions [39d, 42] . Soft donor groups such as S, Se/Br, I coordination bring down the 4 A 2 → 4 T 2 (ligand field states in T d symmetry) transition energy gap, and thus the D switches to negative from positive.…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 70%
“…Particularly, complex [Co{N(SOCN i Pr2 ) 2 } 2 ] ( 32 ) was found to yield a larger D value of −118 cm −1 ; this value was predicted by theory and has not yet been verified by experiments (see Figure 6 d). [12c] The d orbital splitting obtained from AILFT analysis reveals that the dx2-y2 –d xy gap is close to 940 cm −1 and the first excited quartet state lies only 417 cm −1 higher in energy (see Figure 6 e). Other than S donor ligands, an N‐coordinated Co II complex (HNEt 3 ) 2 [Co(L) 2 ] ( 33 ) (where H 2 L=1,2‐bis(methanesulfonamido)benzene), possessing again D 2 d symmetry, was reported by van Slageren and co‐workers, where a huge negative D value (−115 cm −1 ) was confirmed from far‐infrared spectroscopy, CASSCF‐NEVPT2 calculations and other magnetic measurements (see Figure 6 f).…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 94%
See 1 more Smart Citation
“…Deviation from ideal T d symmetry is well-known to result in a significant D value for tetrahedral Co II ions. 35–38 …”
Section: Resultsmentioning
confidence: 99%
“…Deviation from ideal Td symmetry is well-known to result in a significant D value for tetrahedral Co II ions. [35][36][37][38] For complex 7, the orbital degeneracy of the tetrahedral Ni II ion precluded convergence of the DFT calculations and thus no host-guest JNi-Ni exchange coupling could be estimated. NEVPT2 calculations yield a D value of +214 cm −1 for [NiCl4] 2− , a value much larger than that estimated from experimental susceptibility and magnetisation data.…”
Section: Electronic Structure Of the Mx4ni4l6 Cages (2-8)mentioning
confidence: 99%